Needs and Second Nature in Adorno and Marcuse: The Repression of the Individual - Çağmar, Mehmet Şirin (Erzurum Teknik Üniversitesi, 2025)
Every new situation has always given rise to new power relations. These power relations often impose certain conditions on people within the social sphere, within the framework they themselves have determined. The 20th century was a period in which these power relations were largely realized through industrialization and technology. The most fundamental characteristic of this mediation can be described as the conditions it created being driven by specific hegemonic goals. The study will first attempt to expose the role of these goals in oppressing individuals and reveal the rationalities established in the social sphere. It will be demonstrated that the needs of these rationalities are reflected as if they were the individual's true needs. This section of the study will highlight how various hegemonic relations are imposed on individuals through these needs. It will then be argued that the new social and political hegemony created by industrialization and technology, by imposing a second nature on them to prevent any internal conflicts this situation might create, oppresses individuals and forces them to submit easily.

Tüm yeni durumlar her zaman kendi içerisinde yeni güç ilişkilerini doğurmuştur. Bu güç ilişkileri çoğu zaman toplumsal alanda kendisinin belirlediği çerçevede insanlara belirli koşullar dayatmaktadır. 20. Yüzyıl bu güç ilişkilerinin büyük oranda endüstrileşme ve teknoloji ile gerçekleştiği bir dönem olmuştur. Bu dolayımın en temel özelliği her şeyden önce ortaya çıkardığı koşulların belli hegemonik amaçlarca hareket etmesi şeklinde ifade etmek mümkündür. Çalışma öncelikle bu amaçların bireyleri baskılamasındaki rolünü serimlemeye çalışarak toplumsal alanda oluşturulan rasyonaliteleri ortaya koyacaktır. Buradaki rasyonalitelerin gereksinimleri, bireyin gerçek gereksinimleriymiş gibi yansıtıldığı gösterilecektir. Çalışmanın bu kısmı bireylere gereksinimler aracılığıyla çeşitli hegemonik ilişkiler dayatıldığına dikkat çekecektir. Daha sonra ise bu durumun insanlarda yaratacağı herhangi bir içsel çatışmayı önlemek için onlara ikinci bir doğayı dayatarak endüstrileşme ve teknolojinin ortaya çıkardığı yeni toplumsal ve politik hegemonyanın bireyleri baskılayarak onları kolayca itaat ettirmeye zorladığı ifade edilecektir.
Adorno ve Marcuse’de Gereksinimler ve İkinci Doğa: Bireyin Baskılanışı
Keywords: Sociology (Other); Sosyoloji (Diğer)